Growing scientists: a partnership between a university and a school district - Woods, Teresa Marie (Kansas State University, 2012)
Precollege science education in the United States has virtually always been influenced by university scientists to one degree or another. Partnership models for university scientist – school district collaborations are being advocated to replace outreach models. Although the challenges for such partnerships are well documented, the means of fostering successful and sustainable science education partnerships are not well studied. This study addresses this need by empirically researching a unique scientist-educator partnership between a university and a school district utilizing case study methods. The development of the partnership, emerging issues, and multiple perspectives of participants were examined in order to understand the culture of the partnership and identify means of fostering successful science education partnerships. The findings show the partnership was based on a strong network of face-to-face relationships that fostered understanding, mutual learning and synergy. Specific processes instituted ensured equity and respect, and created a climate of trust so that an evolving common vision was maintained. The partnership provided synergy and resilience during the recent economic crisis, indicating the value of partnerships when public education institutions must do more with less. High staff turnover, however, especially of a key leader, threatened the partnership, pointing to the importance of maintaining multiple-level integration between institutions. The instrumental roles of a scientist-educator coordinator in bridging cultures and nurturing the collaborative environment are elucidated. Intense and productive collaborations between teams of scientists and educators helped transform leading edge disciplinary science content into school science learning. The innovative programs that resulted not only suggest important roles science education partnerships can play in twenty-first century learning, but they also shed light on the processes of educational innovation itself. Further, the program and curriculum development revealed insights into areas of teaching and learning. Multiple perspectives of participants were considered in this study, with student perspectives demonstrating the critical importance of investigating student views in future studies. When educational institutions increasingly need to address a diverse population, and scientists increasingly want to recruit diverse students into the fields of science, partnerships show promise in creating a seamless K-20+ continuum of science education.
Keywords: Science education; Secondary education; Partnership; Twenty-first century skills; Animal health; Science Education (0714); Secondary Education (0533)